The Comparison of Student Achievement and Student Activity in Cooperatif Learning With TPS and STAD at Topic of Cell in Senior High School - Nora Alisa Pulungan (Magister Pendidikan Biologi, Universitas Negeri Medan, 2018)
The objective of this research is to know the comparison of student achievement and student activity in cooperative learning with TPS (Think-Pair-Share) and with STAD (Student Teams-Achievement Division) at topic of cell in XI class SMA Negeri 5 Padangsidimpuan on academic year 2017/2018. The population of this research was the whole students of grade XI SMA Negeri 5 Padangsidimpuan in academic year 2017/2018 which consists of 5 classes with the total number of te students are 250 students. The sample of this research was taken by random sampling, where class XI2, 40 students is as the TPS class and class XI3, 40 students, is as the STAD class. The research was conducted by experiment research in which its objective is to know the comparison of applying the two methods. Based on the data analysis. There is difference between the student achievement of TPS class and that of STAD class in which the average score of TPS class is 80,00. Whereas, the average score of STAD class is 71,30. The student activity also taking part on increase of student achievement, where the percentage of students achievement at TPS class are 86%, as for at STAD class are 79 %. It's mean that the students activity gave a good contribution to increase the student achievement. The difference is proven through hypothesis testing by using t-test and the level of significance α = 0,05, where tacc>ttable (4,57>1,99), which means that Ho is rejected and Ha is accepted. Finally it is concluded that there is the difference of student achievement and student activity in cooperative learning with TPS (Think-Pair-Share) and with STAD (Student Teams-Achievement Division) at topic of cell in XI class SMA Negeri 5 Padangsidimpuan.